Diurnal ingestive Behavior of beef cattle on grass hybrid Brachiaria Mulato II (2014)
For cattle production under grazing conditions, the system characteristic is the multiplicity of elements that interact to make meaningful changes in the eating habits of cattle. This study evaluated diurnal behavior and their productive performance. Grazing cattle were fed with hybrid Brachiaria cv. Mulato II. This study was conducted in a 107 days period between July and October 2010 at Corpoica Turipaná Research Center, (Cereté, Colombia). 72 cebú cattle, with an average initial weight of 314 ± 29 kg were used on a 12 hectares field planted with hybrid Brachiaria cv. Mulato II. Two experimental trials were implemented: the first one, using a randomized block design with two replicates using three treatment of 5, 6 and 7 animals/ha. Weight gaining and quality of the fodder were evaluated. The second trial using a randomized block design with three treatments for nine experimental units, monitored daily feeding habits. The quality of the fodder didn’t show any significant difference (P > 0.05), but the time the cattle spent grazing and ruminating while laying down and moving regularly, showed differences (P < 0.05). The weight gaining during the different treatments of daily feeding showed a significant difference: (P > 0.001). The variables of feeding behavior evaluated, and the weight gaining process were highly influenced by the animal performance.